Development of the Latest Technology Based Accounting Information System to Increase Company Efficiency - RUM Hendarmin; Rafika Sari (Jurnal Akuntansi, 2024)
This research explores the impact of developing Accounting Information Systems (AIS) based on cutting-edge technology on company efficiency. We gathered data from questionnaires distributed to companies that have adopted state-of-the-art technology in their AIS. The research results indicate that the use of artificial intelligence (AI) significantly enhances operational efficiency in companies. Companies adopting blockchain technology also achieve higher levels of user satisfaction. User training and company size also have a positive impact on efficiency and better decision-making.In the discussion, we highlight the importance of investing in user training and maintaining state-of-the-art technology. We also acknowledge that implementation costs can be a constraint, particularly for smaller companies. This research has certain limitations, including a sample that may not cover the entire spectrum of industries and company sizes. However, further research can delve deeper through case studies. In the continually evolving business world, the development of AIS based on cutting-edge technology is a key factor in achieving efficiency, better decision-making, and user satisfaction. Companies must understand and address these challenges to attain a competitive edge and long-term success.